ASSISTANCE IN IMPLEMENTING AI TECHNOLOGY IN MANAGING MUHAMMADIYAH SCHOOL SOCIAL MEDIA IN SIDOARJO - Istiqomah, Istiqomah; Aesthetika, Nur Maghfirah; Ainiyah, Indah Nurul; Ifanisari, Irma Fahriza; Wulansari, Fitri Retno (Antis-publisher, 2025)
Objective: This community service activity aims to improve the competence of Muhammadiyah school staff in Sidoarjo in managing social media through the use of artificial intelligence (AI) technology. The main objective of this program is to help schools improve the effectiveness of digital communication, strengthen branding, and reach a wider audience through data-driven content strategies. Method: The method employed is a phased approach over six months, encompassing awareness-raising, technical training, practical sessions, evaluation, and discussion forums. The training introduces various AI tools such as ChatGPT, Hootsuite, Canva, and Google Analytics, which are used in content planning, audience analysis, and publication scheduling. Evaluation is conducted through pre-tests and post-tests for 40 participants to measure improvements in understanding and skills. Results: The results showed a significant 40% increase in the school's social media interactions and an increase in staff confidence in using AI technology. The program also produced creative and consistent promotional content that contributed to enhancing the school's reputation in the community. Novelty: Thus, this mentoring program proved effective in integrating AI technology into the school's digital communication strategy.